Selective depletion of radiolabeled HER2-specific antibody for contrast improvement during PET - Priyanka Khare; Wei Sun; Sreevidhya Ramakrishnan; Rafal Swiercz; Guiyang Hao; Su-Tang Lo; Kien Nham; Xiankai Sun; Raimund J. Ober; E. Sally Ward (Taylor & Francis Group, 2021)
The prolonged in vivo persistence of antibodies results in high background and poor contrast during their use as molecular imaging agents for positron emission tomography (PET). We have recently described a class of engineered Fc fusion proteins that selectively deplete antigen-specific antibodies without affecting the levels of antibodies of other specificities. Here, we demonstrate that these Fc fusions (called Seldegs, for selective degradation) can be used to clear circulating, radiolabeled HER2-specific antibody during diagnostic imaging of HER2-positive tumors in mice. The analyses show that Seldegs have considerable promise for the reduction of whole-body exposure to radiolabel and improvement of contrast during PET.